Enhanced Visible Light Communication for Real-Time Audio With Interference-Resilient Protocols - Kanchana Chathurangi Ahangama; Hemali Pasqual; Chinthaka Premachandra; H. Waruna Haripriya Premachandra (IEEE Access)
Despite its potential for high-speed data transmission, visible light communication (VLC) technology faces significant challenges in achieving reliable real-time audio streaming due to interference, signal degradation, and synchronization issues. These limitations hinder the widespread adoption of VLC technology, especially in high-quality audio transmission. This paper introduces a novel VLC transceiver design incorporating advanced interference-resilient protocols, dynamic frame structuring, and robust error correction algorithms to enhance audio streaming performance. The proposed system achieves a signal-to-noise ratio (SNR) of 45 dB, reduces the bit error rate (BER) by up to four orders of magnitude to $1 × 10^{-6}$ , and lowers the total latency by 50%. Furthermore, synchronization errors are reduced by 66.7%, while the mean opinion score (MOS) reaches 4.8, and the objective difference grade (ODG) improves to -0.5. The comparative analysis demonstrates significant advantages over Wi-Fi (802.11ac), VLC IM/DD, and state-of-the-art VLC systems. These findings establish the proposed system as a reliable solution for real-time, high-fidelity audio applications and a foundation for extending VLC technology to broader domains.